Nature for Development - United Nations Development Programme (United Nations, 2024)
Nature underpins our lives, societies, and economies and is fundamental to achieving our 2030 Agenda. Addressing the nature crisis is essential to eradicating and preventing poverty, reducing inequalities, and protecting human rights. Moreover, nature is a positive source of solutions and hope: a nature-positive transition is central to tackling planetary crises such as climate change. This publication offers entry points to operationalize the opportunity to advance the SDGs through nature. It will help decision-makers and practitioners recognize programming options and make the case for investing in nature to achieve development outcomes. It comprises key facts, figures and talking points about nature through five different practice lenses - Nature for Food Security; Nature for Water Security; Nature for Climate Action; Nature for Gender Equality; Nature for Peace. This is a ‘living’ resource and call to action that will expand to cover more practices.